Princípio federativo como limite à modificação das competências tributárias - Campos, Leonardo Nuñez (2021)
The object of the present doctoral thesis refers to the investigation of the limits imposed by the federative principle to the modification of tax competences. For this purpose, the general aspects of tax competence were analyzed to understand the influence of the federative principle in the construction of the system in the current format. Then, the study of the federative principle and related principles was further developed. In this sense, it was found that, as a stone clause, the federative principle is protected at its essential core, making it possible to modify the constitutional text through an amendment to improve the federation. Afterwards, the relationship between the federative principle and contributions was demonstrated, as well as the potential federative conflicts arising from the use of this tax species, characterized by its purpose. The shocks between federal entities due to the use of tax exemptions to attract investments were also addressed, in order to understand the extent of autonomy and the possibility of its limitation to avoid fiscal wars. It also followed, demonstrating the relationship between the federative principle and tax immunities. Finally, the limitations and possibilities of modifying tax competences to improve the national tax system were highlighted